1988
DOI: 10.3181/00379727-189-42813
|View full text |Cite
|
Sign up to set email alerts
|

Four-Hour Atrial Natriuretic Peptide Infusion in Conscious Rats: Effects on Urinary Volume, Sodium, and Cyclic GMP

Abstract: Atrial natriuretic peptide (ANP) is released from the cardiac atria in response to acute volume loads; when infused acutely ANP causes diuresis and natriuresis. Cyclic GMP (cGMP) appears to be the second messenger for ANP in the kidney. The role that ANP plays in the long-term regulation of salt and water balance is unclear, however, since resistance to ANP's natriuretic and diuretic activity develops during prolonged administration. The purpose of the present study is to examine the relationship between the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…However, as mentioned above, ANP induced increased plasma membrane AQP2 expression. Moreover, the time course of ANP effects on diuresis and water excretion indicate that the effect is transient (6). Thus aldosterone-induced increased ANP secretion is not likely to be involved in the decreased apical AQP2 expression observed in the present study; 2) PGE 2 has been demonstrated to play an important role in antagonizing the effect of vasopressin on osmotic water permeability in the renal collecting duct.…”
Section: Discussionmentioning
confidence: 45%
“…However, as mentioned above, ANP induced increased plasma membrane AQP2 expression. Moreover, the time course of ANP effects on diuresis and water excretion indicate that the effect is transient (6). Thus aldosterone-induced increased ANP secretion is not likely to be involved in the decreased apical AQP2 expression observed in the present study; 2) PGE 2 has been demonstrated to play an important role in antagonizing the effect of vasopressin on osmotic water permeability in the renal collecting duct.…”
Section: Discussionmentioning
confidence: 45%
“…19 Prolonged infusion of ANP in rats was associated with increased natriuresis and diuresis during the first hour, which returned to baseline after 2 hours of infusion. 25 Urinary excretion of cGMP, the second messenger of ANP, remained elevated during ANP infusion, suggesting that the diminishing natriuretic and diuretic effects in response to ANP are independent of cGMP signaling. In addition, a transient increase in natriuresis and diuresis after prolonged ANP infusion was confirmed in healthy men.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, acute ANP infusions significantly increased urinary sodium excretion and peaked 15 min after the onset of ANP infusion and declined gradually after the peak but remained elevated compared with control (42). Of note, several studies have shown that diuresis and natriuresis induced by ANP are transient when ANP is given as continuous infusions or as repeated bolus injections in humans and animals because resistance to the diuretic and natriuretic actions of ANP develops after relatively brief periods of ANP infusion (7,13,41). This phenomenon may be related to the mechanism that the subcellular localization of ENaC increases after 90 min of ANP infusion (42).…”
Section: Discussionmentioning
confidence: 96%